2020
DOI: 10.3390/s20102808
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Solutions for Magnetic Field Problems in Terfenol-D Transducers

Abstract: An appropriate magnetic design helps ensure that the Terfenol-D (Terbium- Dysprosium-Iron alloy) rods in giant magnetostrictive transducers have the perfect magnetostriction ability. To determine the optimum Terfenol-D rod state, a segmented stack configuration comprised by the Terfenol-D rods and NdFeB (neodymium-iron-boron) permanent magnets is presented. The bias magnetic field distributions simulated through the finite element method indicate that the segmented stack configuration is one effective way to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…As a result, the pulling force of the mass ball on the FBG is constantly under axial extension to avoid excessive pulling power, which prevents the FBG from being fatigued. Terfenol-D [ 23 ] is the magnetostrictive material, which possesses superior magnetic characteristics and energy conversion efficiency than pure nickel (Ni) and piezoelectric ceramics (PZT).…”
Section: Structural Design and Methods For Attitude Estimationmentioning
confidence: 99%
“…As a result, the pulling force of the mass ball on the FBG is constantly under axial extension to avoid excessive pulling power, which prevents the FBG from being fatigued. Terfenol-D [ 23 ] is the magnetostrictive material, which possesses superior magnetic characteristics and energy conversion efficiency than pure nickel (Ni) and piezoelectric ceramics (PZT).…”
Section: Structural Design and Methods For Attitude Estimationmentioning
confidence: 99%
“…He [ 15 ] proposed a method to calculate the number of radial slits of the Terfenol-D rod, which reduces the eddy current loss and saves on cost. Teng et al [ 16 ] developed a Terfenol-D transducer; digital slots were set on the Terfenol-D rod to reduce the eddy current loss. Huang et al [ 17 ] cut Terfenol-D into different square rings, studied the changes in its magnetic energy losses under different frequencies and magnetic flux density amplitudes, and analyzed the influence of material anisotropy on the losses.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al (2012) investigated the influence of the eddy current loss on material vibration output characteristics and impedance characteristics between the laminated structure and the monolithic structure, and the results showed that the Terfenol-D rod with laminated structure had smaller eddy current loss and higher eddy current cut-off frequency. Teng and Li (2020) presented digital slots on a Terfenol-D rod to reduce eddy current loss, the simulations reveal that the configuration of the slots decreases the eddy current losses by 78.5% compared to the untreated rod. At present, there are many studies on eddy current loss and eddy current distribution of rods, few studies on the hysteresis loss and its distribution of the rods.…”
Section: Introductionmentioning
confidence: 99%